High energy milling of Cu2O powders - Dodoo-Arhin, D.; Vettori, G.; D’Incau, M.; Leoni, P.; Scardi, P. (Oldenbourg Wissenschaftsverlag, München, 2011)
X-ray diffraction line profile analysis based on the recently developed Whole Powder Pattern Modelling was used to investigate the microstructure changes in Cu2O powders milled in a vibrating cup mill. The reduction in the average size of coherently scattering domains - and simultaneous narrowing of the size distribution - occurs in the first minutes. An asymptotic limit of ca. 10 nm is obtained. The reduction in size is obtained at the expenses of introducing a massive quantity of dislocations in the system, reaching a limit of ca. 4×10-16 m-2. A proper nanocrystalline microstructure can be obtained for a milling of ca. 20 min.
Keywords: Diffraction; High Energy Milling; Whole Powder Pattern Modelling